Building a Solid Business Foundation by Implementing Appropriate Financial Reporting, Directed Marketing, and Attractive Branding for Sukawati Wood Carving Entrepreneurs - Gede sanjaya adi PUTRA; I Wayan Gede SARMAWA; Ida Bagus Made Putra MANUABA (PT Keberlanjutan Strategis Indonesia, 2025)
Gianyar Regency, Bali, is known as a center for high-value woodcarving crafts. However, MSMEs in this sector still face several challenges in business management, particularly in financial record-keeping, branding strategies, and digital marketing. This community service program aims to increase the business capacity of the Baliary Artcrafts woodworking group through a digital-based empowerment approach. The methods used include training in simple financial record-keeping using Excel and accounting applications, strengthening brand identity through logo and product packaging design, and digital marketing training utilizing social media and e-commerce. The program also involves university students as a form of implementing the Independent Learning Campus (MBKM) program and supporting the achievement of higher education's Key Performance Indicators (IKU). The expected outcomes of this activity are increased financial literacy, a more professional brand image, and broader market reach for the target MSMEs. Overall, this activity contributes to the digital transformation of MSMEs in the craft sector in Gianyar, making them more adaptive and competitive in the global market.